1997
DOI: 10.1016/s0006-3495(97)78136-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal unfolding in a GCN4-like leucine zipper: 13C alpha NMR chemical shifts and local unfolding curves

Abstract: 13C alpha chemical shifts and site-specific unfolding curves are reported for 12 sites on a 33-residue, GCN4-like leucine zipper peptide (GCN4-lzK), ranging over most of the chain and sampling most heptad positions. Data were derived from NMR spectra of nine synthetic, isosequential peptides bearing 99% 13C alpha at sites selected to avoid spectral overlap in each peptide. At each site, separate resonances appear for unfolded and folded forms, and most sites show resonances for two folded forms near room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 28 publications
6
95
0
Order By: Relevance
“…The greatest stability gains were observed at chain lengths of 3 heptads; further increases in length were stabilizing but to lesser degrees. This is primarily because of end fraying, a partial and temporary unfolding of the helix termini (52,82,83). We found that an increase from 3 to 4 heptads caused an increase in stability of 4.06 kcal/mol for the ISAL sequence and an increase of 3.86 kcal/mol for the VAAL sequence.…”
Section: Heptads (B) Vaal 3 Heptads (C) Vaal 4 Heptads (D) Isal 3 mentioning
confidence: 77%
“…The greatest stability gains were observed at chain lengths of 3 heptads; further increases in length were stabilizing but to lesser degrees. This is primarily because of end fraying, a partial and temporary unfolding of the helix termini (52,82,83). We found that an increase from 3 to 4 heptads caused an increase in stability of 4.06 kcal/mol for the ISAL sequence and an increase of 3.86 kcal/mol for the VAAL sequence.…”
Section: Heptads (B) Vaal 3 Heptads (C) Vaal 4 Heptads (D) Isal 3 mentioning
confidence: 77%
“…This demonstrated that the contribution of Leu-Leu hydrophobic interactions to the stability of the coiled-coil structure were less important at the ends of the coiled-coil, and that the ends of the coiled-coil were more flexible. More recently, Holtzer et al (65) clearly demonstrated by 13 C R chemical shifts that such an end-fraying also occurred in a GCN4-like leucine zipper. All these studies suggest that the different heptads which make up a dimeric coiled-coil structure contribute differently to its stability; the heptads located at the ends of the coiled-coil are able to fray whereas the ones composing the core of the coiled-coil are more stable due to the tighter packing of the hydrophobic residues.…”
Section: Discussionmentioning
confidence: 96%
“…56,57 Thirdly, secondary chemical shifts in unfolded proteins were found to almost be in the range expected for a-helical residues. 58 Whatever the structure of this middle segment is, it is incompatible with the adoption of a uniform in-register b-sheet structure as demonstrated by 1D-solid-state NMR studies on selectively 13 CO-labeled scrapie prion-seeded Syrian hamster recPrP (90-231)-fibrils. 15 (iii) A b-sheet-core C-terminal of »155 is consistent with the finding that Tyr152-Arg154 remains flexible during fibrillation, whereas Tyr165-Arg167 is part of the rigid core.…”
Section: Discussionmentioning
confidence: 99%